PTH-066 Post-marketing experience of vedolizumab: pneumonia and other respiratory tract infections. (17th June 2017) - Bhayat, F; Blake, A; Travis, SP
Abstract : Introduction: Vedolizumab (VDZ) is a humanised monoclonal antibody that binds to α4 β7 integrin, selectively blocking gut-specific lymphocyte trafficking. Gut selectivity may reduce infection risk compared with anti-tumour necrosis factor-alpha (TNFα) agents, which cause systemic immunosuppression. The annual pneumonia rate in inflammatory bowel disease patients is higher than in healthy individuals (13.8/1000 vs 7.6/1000; incident rate ratio 1.82; 95% CI: 1.75–1.88) 1 and the risk is greater with anti-TNFα treatment (odds ratio 1.28; 95% CI: 1.08–1.52). 1 Here, we describe respiratory tract infections (RTIs) reported with VDZ therapy in the post-marketing (PM) setting. Method: PM VDZ safety data from the Global Safety Database (May 2014 to May 2016) were reviewed for reports of lower RTIs (LRTIs) and upper RTIs (URTIs; MedDRA v19.0 High Level Terms: 'LRT and lung infections', 'LRTIs not elsewhere classified [NEC]', 'URTIs' and 'URTIs NEC'). Results: In the context of 46 978 patient-years in the PM setting, 40 serious and 68 non-serious LRTI events were reported in 106 patients; 54 patients had pneumonia (34 serious) equivalent to1 event/1000 patient-years of therapy. Regarding potential risk factors for pneumonia, 2 patients had surgery ≤30 days prior to the event (not reported [NR] in 47/54 patients). Six patients with LRTIs were current/former smokers (NR: 96/106), 53/74 and 26/74 reported prior/concomitant anti-TNFα and immunomodulator use respectively (NR: 32/106). Most LRTIs occurred ≥2 months after the first VDZ infusion (32/44 events; NR: 64 events). VDZ treatment was continued in most patients (n=61/89; NR: 17/106) reporting LRTIs. There were 4 serious and 313 non-serious URTIs in 300 patients; nasopharyngitis was most frequently reported (201 events). Most URTIs occurred ≥2 months after the first VDZ infusion (77/135 events; NR: 182 events). VDZ treatment was continued in most patients (n=229/257; NR: 43/300) experiencing URTIs. Conclusion: During 46 978 patient-years of VDZ therapy, RTIs (including pneumonia) were infrequent and most patients continued VDZ. No new trends were identified in the characterisation of RTIs from PM experience with VDZ. Limitations associated with PM safety reporting must be considered when interpreting these results. References: . Long MD, et al. Am J Gastroenterol2013;108:240 Disclosure of Interest: F. Bhayat Conflict with: Takeda Development Centre Europe Ltd, A Blake Conflict with: Takeda Development Centre Europe Ltd, S Travis Conflict with: AbbVie, IOIBD, Lilly, UCB, Vifor, and Norman Collison Foundation, Conflict with: AbbVie, Amgen, Biogen, Boehringer Ingelheim, Bristol-Myers Squibb, Celgene, Chemocentryx, Cosmo, Ferring, Giuliani SpA, GlaxoSmithKline, Janssen, Lilly, MSD, Neovacs, NovoNordisk, Norman Collison Foundation, Novartis, NPS Pharmaceuticals, Pfizer, Proximagen, Receptos, Shire, Sigmoid Pharma, Takeda, Topivert, UCB, VHsquared and Vifor, Conflict with: Oxford University Hospitals NHS Foundation Trust and the University of Oxford, Conflict with: Lecture fee(s): AbbVie, Amgen, Biogen, Ferring, Takeda